Investigation of scanning parameters for thyroid fine needle aspiration cytology specimens: A pilot study - Maheswari S Mukherjee; Amber D Donnelly; Elizabeth R Lyden; Whitney R Wedel; Mary F McGaughey; John J Baker; Stanley J Radio (Elsevier, 2015)
Background: Interest in developing more feasible and affordable applications of virtual microscopy in the field of cytology continues to grow. Aims: The aim of this study was to investigate the scanning parameters for the thyroid fine needle aspiration (FNA) cytology specimens. Subjects and Methods: A total of twelve glass slides from thyroid FNA cytology specimens were digitized at ×40 with 1 micron (μ) interval using seven focal plane (FP) levels (Group 1), five FP levels (Group 2), and three FP levels (Group 3) using iScan Coreo Au scanner (Ventana, AZ, USA) producing 36 virtual images (VI). With an average wash out period of 2 days, three participants diagnosed the preannotated cells of Groups 1, 2, and 3 using BioImagene's Image Viewer (version 3.1) (Ventana, Inc., Tucson, AZ, USA), and the corresponding 12 glass slides (Group 4) using conventional light microscopy. Results: All three raters correctly identified and showed complete agreement on the glass and VI for: 86% of the cases at FP Level 3, 83% of the cases at both the FP Levels 5 and 7. The intra-observer concordance between the glass slides and VI for all three raters was highest (97%) for Level 3 and glass, same (94%) for Level 5 and glass; and Level 7 and glass. The inter-rater reliability was found to be highest for the glass slides, and three FP levels (77%), followed by five FP levels (69.5%), and seven FP levels (69.1%). Conclusions: This pilot study found that among the three different FP levels, the VI digitized using three FP levels had slightly higher concordance, intra-observer concordance, and inter-rater reliability. Scanning additional levels above three FP levels did not improve concordance. We believe that there is no added benefit of acquiring five FP levels or more especially when considering the file size, and storage costs. Hence, this study reports that FP level three and 1 μ could be the potential scanning parameters for the thyroid FNA cytology specimens.